The SBAR Communication Method (Situation-Background-Assessment-Recommendation) In Nursing: A Literature Review - Putri, Prestasianita; Afandi, Alfid Tri (Jurnal Kesehatan Komunitas Indonesia, 2023)
Effective communication can majorly impact patients and families as it can influence their care. SBAR communication is used inefficiently, effectively, and accurately to convey information to others to achieve skills in critical, structured thinking and increase patient safety. Communication disorders between nurses can hinder the nursing process and the goals of nursing care. This literature review method uses the method of searchingfrom journals, textbooks, e-books, study (original research) relating to the positive impact of SBAR communication in nursing, which can later be used in improving patient care, improving team performance, and management, as well as increasing the delivery of information handover. The results of the literature review found that communication is very important in the service setting. So that the hope can increase patient and family satisfaction when getting optimal service from nurses. Nursing services are always inseparable from how to communicate properly, so it is very important for this communication to be implemented optimally.